Suppressor CD4+ T cells expressing HLA-G are expanded in the peripheral blood from patients with acute decompensation of cirrhosis. Issue 6 (3rd August 2021) - Khamri, Wafa; Gudd, Cathrin; Liu, Tong; Nathwani, Rooshi; Krasniqi, Marigona; Azam, Sofia; Barbera, Thomas; Trovato, Francesca M; Possamai, Lucia; Triantafyllou, Evangelos; Seoane, Rocio Castro; Lebosse, Fanny; et al.
Abstract : Objective: Identifying components of immuneparesis, a hallmark of chronic liver failure, is crucial for our understanding of complications in cirrhosis. Various suppressor CD4 + T cells have been established as potent inhibitors of systemic immune activation. Here, we establish the presence, regulation and mechanism of action of a suppressive CD4 + T cell subset expressing human leucocyte antigen G (HLA-G) in patients with acute decompensation of cirrhosis (AD). Design: Flow cytometry was used to determine the proportion and immunophenotype of CD4 + HLA-G + T cells from peripheral blood of 20 healthy controls (HCs) and 98 patients with cirrhosis (28 with stable cirrhosis (SC), 20 with chronic decompensated cirrhosis (CD) and 50 with AD). Transcriptional and functional signatures of cell-sorted CD4 + HLA-G + cells were delineated by NanoString technology and suppression assays, respectively. The role of immunosuppressive cytokine interleukin (IL)-35 in inducing this population was investigated through in vitro blockade experiments. Immunohistochemistry (IHC) and cultures of primary human Kupffer cells (KCs) were performed to assess cellular sources of IL-35. HLA-G-mediated T cell suppression was explored using neutralising antibodies targeting co-inhibitory pathways. Results: Patients with AD were distinguished by an expansion of a CD4 + HLA-G + CTLA-4 + IL-35 + immunosuppressive population associated with disease severity, clinical course of AD, infectious complications and poor outcome. Transcriptomic analyses excluded the possibility that these were thymic-derived regulatory T cells. IHC analyses and in vitro cultures demonstrate that KCs represent a potent source of IL-35 which can induce the observed HLA-G + phenotype. These exert cytotoxic T lymphocyte antigen-4-mediated impaired responses in T cells paralleled by an HLA-G-driven downregulation of T helper 17-related cytokines. Conclusion: We have identified a cytokine-driven peripherally derived suppressive population that may contribute to immuneparesis in AD.